Towards a comprehensive, integrative analysis of the diversity of European microplaninid land flatworms (Platyhelminthes, Tricladida, Microplaninae), with the description of two peculiar new species. Issue 1 (2nd January 2016) - Sluys, Ronald; Mateos, Eduardo; Riutort, Marta; Álvarez-presas, Marta
Abstract : The present study forms a first and major step towards a comprehensive morphological and molecular analysis of the species diversity of European microplaninid land planarians by presenting a molecular phylogenetic tree on the basis of alignments of the mitochondrial Cox1 gene from 158 specimens as well as a concatenated phylogeny (Cox1 and 18S genes) on the basis of 41 sequences for nine Microplana species included in this study. Genetic distances between and within known and new species were calculated. Combined morphological and molecular results facilitated an integrative delimitation of new species as well as the diagnosis of new populations of already known species. An integrative account is provided of two new and aberrant species from the Iberian Peninsula and southern France. Through the molecular approach a Confirmed Candidate Species was detected among the newly sampled populations. Further we document samples from new localities for five already known species as well as new sites for the Confirmed Candidate Species. The new data considerably expand the European range of several already known species included in the present study. The results of an in-depth study of the taxonomic literature, as well as original material, are documented since this was required for appropriate identification of the new materials. This part of the study resulted in a re-evaluation of the taxonomic status of several nominal species and in the following taxonomic conclusions: Rhynchodemus pyrenaicus is a species of Microplana and not Rhynchodemus ; Rhynchodemus attemsi, R. peneckei, and R. henrici should be transferred to the genus Microplana ; Microplana attemsi and M. peneckei are not junior synonyms of M. henrici ; Microplana styriaca is not a synonym of M. terrestris ; Rhynchodemus howesi is not a junior synonym of M. pyrenaica and belongs to the genus Rhynchodemus and not to Microplana ; Microplana richardi is not a synonym of M. terrestris. The current diagnosis of the genus Microplana should be amended such that it refers to the situation that the species generally have two small eyes but occasionally may have multiple eyes. http://zoobank.org/urn:lsid:zoobank.org:pub:22B437AA-9D41-4DA0-AE3C-BD8F636CB96D